Patient understanding of oral information: Self-assessment versus test/feedback. Issue 9 (September 2022) - Wach, Karine; Remen, Thomas; Claudot, Frédérique
Abstract: Objectives: The primary objective of the study was to assess the agreement between the perceived and objectified comprehension levels of oral information received by patients during their preoperative consultation. Methods: We conducted a prospective study in a surgical consultation service with patients who had scheduled prosthetic surgery. The study included 2 measurement phases, each of which involved an evaluation of the patient's perceived understanding and an evaluation of the understanding by a health professional (i.e., objective understanding). Results: The study included 98 patients. Median (min-max) age was 67 (29–90) years. Depending on the item considered, the weighted kappa coefficient for agreement between perceived patient understanding and professional-objectified levels of understanding ranged from 0.05 to 0.42, suggesting low to moderate levels of agreement. In situations of disagreement, patients had higher self-ratings of understanding than practitioners' ratings for most items. Conclusion: Self and hetero-measurement permits the HP to see "how much the patient understands" and to clear up any important element of management both from the point of view of the patient's legal autonomy (self-determination and choice) and of his or her power to act (management of his or her illness). Practice implications: Asking patients if they have understood the information given is insufficient not only from both a medical care but also from a medico-legal point of view. Highlights: The study that in situations of disagreement, patients had higher self-ratings of understanding than practitioners' ratings for most items. Asking patients if they have understood the information given is insufficient. Perceived and objectified measurement can ensure patient's capacity for self-management. A double measurement can also ensure validity of consent.